Anti-fake super-hydrophobic composite film with green I-III-VI multi-element quantum dot microspheres as luminescent material and preparation method of anti-fake super-hydrophobic composite film
By microsphereizing Ag-In-Zn-S quantum dots and coating silica, and combining with silane coupling agent and surfactant, an anti-counterfeiting composite film with superhydrophobic properties was prepared, which solved the problem of the decrease in luminescent intensity of the luminescent material in humid environments, and achieved high stability and high luminescent intensity.
Patent Information
- Application Number
- CN202411807012.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-28
AI Technical Summary
The existing luminescent materials are easily disturbed in the luminescence process in humid environments, and their luminescence intensity decreases, and they are prone to agglomeration during the film formation process, resulting in a decrease in the luminescence intensity.
By synthesizing green I-III-VI multivariate quantum dots Ag-In-Zn-S, microspheres, coated with silica to prevent agglomeration, and synergistically combined with low-surface energy silane coupling agent and surfactant, an anti-counterfeiting light-emitting composite film with superhydrophobic properties was prepared.
It effectively protects the luminescence process from external environment, avoids quantum dot agglomeration, improves the stability and luminescence intensity of the composite film, and realizes a simple and low-cost preparation process.
Smart Images

Figure BDA0005179523260000091 
Figure HDA0005179523280000011 
Figure HDA0005179523280000012
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of quantum dot materials, and in particular to an anti-counterfeiting super-hydrophobic composite film using quantum dot microspheres as luminescent materials and a preparation method thereof. Background Art
[0002] With the development of science and technology and the progress of society, people's lives are constantly enriched and improved, and many valuable commodities are flooding into the market. On the other hand, due to the limitations of anti-counterfeiting technology, counterfeiting has become an increasingly serious global problem, causing great losses to governments, enterprises and individuals. Therefore, improving anti-counterfeiting technology is a difficult problem that needs to be solved urgently.
[0003] Luminescent anti-counterfeiting is a technology that uses luminescent materials to absorb energy and transition to an excited state under specific light irradiation. When it returns to the ground state from the excited state, it produces light of different colors to achieve anti-counterfeiting. It has the characteristics of fast, efficient and low cost. However, the luminescence process of luminescent materials is easily disturbed, and the luminescence intensity is easily affected by the external environment. On the other hand, most of the current luminescent materials such as organic dyes and rare earth metals are high in cost or contain toxic elements, which limits the promotion of luminescent anti-counterfeiting technology. Ag-In-Zn-S quaternary quantum dots do not contain toxic heavy metals such as cadmium and lead, and have a high light absorption coefficient. They are widely used in medical imaging and other fields. However, like other luminescent materials, the luminescence process of Ag-In-Zn-S quaternary quantum dots is easily disturbed and the luminescence intensity decreases in complex environments such as humidity. On the other hand, when the functional materials are prepared by simple and efficient methods such as spraying or coating, Ag-In-Zn-S quantum dots are easy to agglomerate during the film formation process, resulting in a decrease in luminescence intensity. Previously, in CN202410384535.7, a fluorescent super-hydrophobic composite film and its preparation method using fluorinated quaternary quantum dots as fluorescent materials, fluorinated quaternary quantum dots, silica microspheres and sodium dodecyl sulfate were added to ethyl acetate, and evenly dispersed by ultrasonic vibration to obtain a fluorescent super-hydrophobic emulsion to prepare a super-hydrophobic composite film. However, it is still difficult to avoid the problem of quantum dot agglomeration, and direct hydrophobic modification of quantum dots easily causes quantum dot agglomeration, resulting in a decrease in luminescence intensity. Summary of the invention
[0004] In order to solve the problem in the background technology, the present invention first synthesizes green I-III-VI multi-quantum dots Ag-In-Zn-S, then microspheroidizes it, and coats silica on the quantum dots to avoid large-scale agglomeration of the quantum dots. At the same time, the introduction of the silica shell effectively protects the Ag-In-Zn-S luminescence process from being disturbed by the external environment. On the other hand, the Ag-In-Zn-S microspheres are synergistically combined with low-surface-energy silane coupling agents and surfactants to prepare an anti-counterfeiting luminescent composite film with stable super-hydrophobic properties, further improving the stability of the anti-counterfeiting composite film.
[0005] The anti-counterfeiting super-hydrophobic composite film provided by the present invention is prepared according to the following steps:
[0006] (1) Preparation of green I-III-VI multi-element quantum dot microspheres
[0007] 1) Preparation of silver and indium precursor solution: silver nitrate, indium acetate, octadecene, oleic acid and n-dodecyl mercaptan are mixed, heated to 100-130° C. under a nitrogen atmosphere, stirred for 80-100 minutes, and set aside;
[0008] The mass ratio of silver nitrate, indium acetate, octadecene, oleic acid and n-dodecyl mercaptan is 1:3-20:700-2000:4-16:60-300, and the preferred mass ratio is 1:6:750:7:100.
[0009] 2) Preparation of sulfur precursor solution: Mix sublimed sulfur, octadecene and oleylamine, heat to 80-100° C., stir for 50-70 minutes, and set aside;
[0010] The mass ratio of sublimated sulfur, octadecene and oleylamine is 1:7-15:12-25, and more preferably 1:10:20.
[0011] 3) Preparation of zinc precursor solution: Mix zinc stearate, octadecene and oleylamine, heat to 90-110° C., stir for 70-90 minutes, and set aside;
[0012] Wherein, the mass ratio of zinc stearate, octadecene and oleylamine is 1:1-4:1-4, and more preferably 1:2:2.
[0013] 4) Add the sulfur precursor solution prepared in step (2) to the silver and indium precursor solutions prepared in step (1), and stir for 30 to 50 minutes.
[0014] 5) Add the zinc precursor solution prepared in step (3) to the reaction system in step (4), heat to 180-200° C., and stir for 40-60 min.
[0015] 6) The solution of step (5) was cooled to room temperature, poured into ethanol, and centrifuged at 8000 r / min for 5 min to collect the precipitate. After the precipitate was dissolved in n-hexane, it was poured into ethanol and centrifuged again. The process was repeated 3 times to synthesize Ag-In-Zn-S quantum dots.
[0016] 7) Adding Ag-In-Zn-S quantum dot nanoparticles to dichloromethane, and then adding to a hexadecyltrimethylammonium bromide solution, heating to 70-80° C. and keeping the temperature for 25-35 minutes to obtain a modified Ag-In-Zn-S quantum dot solution;
[0017] 8) The modified Ag-In-Zn-S quantum dot solution in step 7) is mixed with the NaOH aqueous solution, heated and mixed at 70-90° C. for 15-25 minutes, and then tetraethoxysilane and ethyl acetate are added, and stirring is continued for 7-9 hours. After the temperature drops to room temperature, centrifugation is performed, and the obtained product is washed with anhydrous ethanol to obtain Ag-In-Zn-S quantum dot microspheres.
[0018] Wherein, the mass ratio of Ag-In-Zn-S quantum dot nanoparticles to tetraethoxysilane is 1:60-600, and more preferably 1:200.
[0019] The relative dosage of Ag-In-Zn-S quantum dot nanoparticles and hexadecyltrimethylammonium bromide is 1 g:0.125 mol.
[0020] The mass ratio of Ag-In-Zn-S quantum dot nanoparticles to tetraethoxysilane is 1:60-600. It is further preferred that the mass ratio of Ag-In-Zn-S quantum dot nanoparticles to tetraethoxysilane is 1:200-300. Too little or too much tetraethoxysilane will greatly affect the hydrophobic properties and stability of the composite film, depending on the thickness and size of the coating.
[0021] The present invention uses a silane coupling agent and a fluorinated surfactant in a mixed form, which not only further reduces the surface energy but also improves the stability of the hydrophobic property compared to using a single agent.
[0022] (2) Preparation of anti-counterfeiting dispersion
[0023] Ag-In-Zn-S quantum dot microspheres, silane coupling agent and fluorine-containing surfactant are added into ethyl acetate and dispersed evenly by ultrasonic vibration to obtain a fluorescent super hydrophobic emulsion.
[0024] Among them, the mass ratio of Ag-In-Zn-S quantum dot microspheres, silane coupling agent, and fluorine-containing surfactant is 1:0.5-2:1-3, and more preferably 1:1:2.
[0025] Among them, the silane coupling agent is one or more of trimethoxy (3,3,3-trifluoropropyl) silane, 1H,1H,2H,2H-perfluorodecyltriethoxysilane, and trimethoxy (1H,1H,2H,2H-tridecafluorooctyl) silane; the fluorine-containing surfactant is one or more of perfluorohexylethyl sulfonic acid, hexafluoroisopropanol, and perfluorooctylethyl acrylate.
[0026] (3) Preparation of anti-counterfeiting super-hydrophobic composite film: spray the anti-counterfeiting dispersion prepared in step (2) onto a flexible substrate, and dry at 80-90° C. for 5-7 hours to obtain a super-hydrophobic composite film with anti-counterfeiting properties.
[0027] The above method has the following technical advantages:
[0028] The core of the multi-element quantum dot microspheres prepared by the present invention is luminous Ag-In-Zn-S quantum dots, and the shell is silicon dioxide. This structure is beneficial to protecting the luminescence process of the quantum dots from being disturbed by the external environment; the anti-counterfeiting luminous composite film prepared by the present invention also has super-hydrophobic properties, which is beneficial to further improve the stability of the composite film; the present invention adopts a spraying method to prepare the anti-counterfeiting super-hydrophobic composite film, and the equipment is simple and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Transmission electron microscope image of Ag-In-Zn-S quantum dots prepared in Example 1
[0030] Figure 2 This is a picture of the water contact angle of the anti-counterfeiting super-hydrophobic composite film prepared in Example 1.
[0031] Figure 3 The fluorescence spectra of the anti-counterfeiting super-hydrophobic composite films prepared in Example 1 and Comparative Example 1 are shown.
[0032] Figure 4 These are pictures of the anti-counterfeiting super-hydrophobic composite film prepared in Example 1 under sunlight and ultraviolet light (365 nm). DETAILED DESCRIPTION
[0033] In order to explain the present invention more clearly, the present invention is further described below in conjunction with embodiments. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0034] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods. The experimental materials, reagents, etc. used in the following experimental examples can be obtained through commercial channels or known experimental methods.
[0035] Example 1
[0036] (1) Preparation of Ag-In-Zn-S quantum dot microspheres
[0037] 1) Preparation of silver and indium precursor solutions: 20 mg of silver nitrate, 120 mg of indium acetate, 15 g of n-octadecene, 140 mg of oleic acid and 2 g of n-dodecyl mercaptan were mixed, heated to 120° C. under atmosphere, stirred for 90 minutes and set aside.
[0038] 2) Preparation of sulfur precursor solution: 20 mg of sublimed sulfur, 200 mg of octadecene and 400 mg of oleylamine were mixed, heated to 90° C., stirred for 60 minutes, and set aside.
[0039] 3) Preparation of zinc precursor solution: 150 mg zinc stearate, 300 mg octadecene and 300 mg oleylamine were mixed, heated to 100° C., stirred continuously for 80 minutes and set aside.
[0040] 4) Add the sulfur precursor solution prepared in step 2) to the precursor solution prepared in step 1), stir for 40 minutes, and set aside.
[0041] 5) Add the zinc precursor solution prepared in step (3) to the reaction system in step (4), heat to 190° C., stir for 50 min, and set aside.
[0042] 6) The solution of step (5) was cooled to room temperature, poured into ethanol, and centrifuged at 8000 r / min for 5 min to collect the precipitate. After the precipitate was dissolved in n-hexane, it was poured into ethanol and centrifuged again. The process was repeated 3 times to synthesize Ag-In-Zn-S quantum dots.
[0043] 7) Add 1 mL of dichloromethane solution containing 10 mg of Ag-In-Zn-S quantum dot nanoparticles to 5 mL of 0.25 M hexadecyltrimethylammonium bromide solution and stir for 30 minutes, then heat to 75°C and keep warm for 30 minutes.
[0044] 8) 1 mL of the solution prepared in step (7) was mixed with 10 μL of a 2M NaOH aqueous solution, heated at 80°C for 20 minutes, and then 0.4 g of tetraethoxysilane and 3 mL of ethyl acetate were injected and stirred for 8 hours. After the temperature dropped to room temperature, the mixture was centrifuged at 9000 r / min for 25 minutes, and the obtained product was washed with anhydrous ethanol to obtain Ag-In-Zn-S quantum dot microspheres.
[0045] (2) Preparation of anti-counterfeiting dispersion
[0046] 30 mg of quantum dot microspheres, 30 mg of trimethoxy (1H, 1H, 2H, 2H-tridecafluorooctyl) silane, and 60 mg of perfluorohexyl ethyl sulfonic acid were added to 50 mL of ethyl acetate, and dispersed evenly by ultrasonic vibration to obtain an anti-counterfeiting dispersion.
[0047] (3) Preparation of anti-counterfeiting super-hydrophobic composite film
[0048] The anti-counterfeiting dispersion prepared in step (2) is sprayed onto the polyimide substrate and dried at 85° C. for 6 hours to obtain a super-hydrophobic composite film with anti-counterfeiting properties.
[0049] Example 2
[0050] The difference between this embodiment and embodiment 1 is that the mass of indium acetate used in step (1) is 150 mg, and the other processing methods are consistent with those in embodiment 1.
[0051] Example 3
[0052] The difference between this embodiment and embodiment 1 is that the mass of sublimated sulfur used in step (1) is 30 mg, and the other treatment methods are consistent with those in embodiment 1.
[0053] Example 4
[0054] The difference between this embodiment and embodiment 1 is that the mass of zinc stearate used in step (1) is 200 mg, and the other processing methods are consistent with those in embodiment 1.
[0055] Example 5
[0056] The difference between this embodiment and embodiment 1 is that the mass of n-dodecyl mercaptan used in step (1) is 2.5 g, and the other processing methods are consistent with those in embodiment 1.
[0057] Example 6
[0058] The difference between this embodiment and embodiment 1 is that the silane coupling agent used in step (2) is 1H,1H,2H,2H-perfluorodecyltriethoxysilane, and the other treatment methods are consistent with those in embodiment 1.
[0059] Example 7
[0060] The difference between this embodiment and embodiment 1 is that the surfactant used in step (2) is perfluorooctyl ethyl acrylate, and the other treatment methods are consistent with those in embodiment 1.
[0061] Example 8
[0062] The difference between this embodiment and embodiment 1 is that the mass of methoxy(1H,1H,2H,2H-tridecafluorooctyl)silane used in step (2) is 45 mg, and the other processing methods are consistent with those in embodiment 1.
[0063] Example 9
[0064] The difference between this embodiment and embodiment 1 is that the mass of perfluorohexyl ethyl sulfonic acid used in step (2) is 70 mg, and the other processing methods are consistent with those in embodiment 1.
[0065] Comparative Example 1
[0066] The difference between Comparative Example 1 and Example 1 is that the luminescent material used in step (2) is not microspheroidized, and the anti-counterfeiting super-hydrophobic composite film is directly prepared by the method of Ag-In-Zn-S quantum dots + silica microspheres.
[0067] Preparation of anti-counterfeiting dispersion:
[0068] 0.5 mg of quantum dots, 25.5 mg of silica microspheres, 30 mg of trimethoxy (1H, 1H, 2H, 2H-tridecafluorooctyl) silane, and 60 mg of perfluorohexyl ethyl sulfonic acid were added to 50 mL of ethyl acetate and dispersed evenly by ultrasonic vibration to obtain an anti-counterfeiting dispersion. Other treatment methods were consistent with Example 1.
[0069] Comparative Example 2
[0070] The difference between this comparative example and Example 1 is that the mass of tetraethoxysilane used in step (1) is 150 mg, and the other processing methods are consistent with Example 1.
[0071] Comparative Example 3
[0072] The difference between this comparative example and Example 1 is that the mass of tetraethoxysilane used in step (1) is 1.1 g, and the other processing methods are consistent with those in Example 1.
[0073] Comparative Example 4
[0074] The difference between this comparative example and Example 1 is that the mass of trimethoxy(1H,1H,2H,2H-tridecafluorooctyl)silane used in step (2) is 18 mg, and the other processing methods are consistent with Example 1.
[0075] Comparative Example 5
[0076] The difference between this comparative example and Example 1 is that the mass of perfluorohexylethylsulfonic acid used in step (2) is 35 mg, and the other processing methods are consistent with Example 1.
[0077] Luminescence performance test: A fluorescence spectrometer (Hitachi, F-4500) was used, and the test range was 200-800nm. Luminescence performance: The fluorescence intensity of the composite film prepared in Example 1 (before stability test) at 620nm was used as the benchmark, and other luminescence performances were the ratio of the intensity of the measured fluorescence curve at 620nm divided by the benchmark.
[0078] Super hydrophobic performance measurement: The contact angle test was performed using a JC2000D1 contact angle tester. The volume of the test liquid was 5 μL. Five sites on the film surface were tested and the average value was calculated, which was the water contact angle of the sample. If the contact angle was greater than 150°, it was a super hydrophobic surface.
[0079] High temperature resistance test: After heating the composite film to 150°C and maintaining it for 30 minutes, the water contact angle and luminescence performance were tested.
[0080] Weather resistance test: After the composite film was placed in an environment with a temperature of 30°C and an air humidity of 70% for 3 months, the water contact angle and luminescence performance were tested.
[0081] UV resistance test: After the composite film is irradiated under a UV lamp with a wavelength of 365nm and a power of 18W for 30 days, the water contact angle and luminescence performance are tested.
[0082] Friction resistance test: Under a load of 100g, the composite film was dragged over 1200-grit sandpaper at a speed of 1cm / s and a distance of 5m. After the test, the water contact angle and luminescence performance were tested.
[0083] The above test results are shown in Table 1 below:
[0084] Table 1
[0085]
[0086] As can be seen from Table 1, it can be seen from Examples 1-9 that the composite film prepared by this method not only has luminescent properties for anti-counterfeiting, but also has super hydrophobic properties, and also shows excellent stability. As can be seen from Examples 1-9 and Comparative Example 1, compared with directly using quantum dots as luminescent materials, using microspheroidized quantum dots as luminescent materials effectively improves the luminous intensity of the composite film. As can be seen from Examples 1-9 and Comparative Example 1, direct hydrophobic modification of quantum dots easily causes quantum dot agglomeration, and the luminous intensity decreases, while hydrophobic modification after microspheroidization can avoid large-scale agglomeration of quantum dots. As can be seen from the comparison with Comparative Examples 2-3, the amount of tetraethoxysilane used is too little or too much, which will greatly affect the hydrophobic properties and stability of the composite film. As can be seen from the comparison of Examples 1-9 and Comparative Examples 4-5, the amount of low surface energy silane coupling agent and surfactant also plays an important role in the hydrophobic properties and stability of the composite film.
[0087] In summary, the composite film prepared by the present invention not only has super hydrophobic and luminescent properties, but also has excellent stability.
[0088] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment, it is not used to limit the present invention. Any technician familiar with this patent can make some changes or modify the technical contents suggested above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the solution of the present invention.
Claims
1. An anti-counterfeiting super-hydrophobic film, characterized in that: The anti-counterfeiting super-hydrophobic composite film is prepared by mixing I-III-VI multi-element quantum dot microspheres with a silane coupling agent and a fluorine-containing surfactant to prepare an anti-counterfeiting dispersion, and then spraying the dispersion on the surface of a polymer substrate to obtain an anti-counterfeiting super-hydrophobic film with luminescent properties; wherein the I-III-VI multi-element quantum dot microspheres are Ag-In-Zn-S quantum dots obtained by silica microspheroidization.
2. The anti-counterfeiting super-hydrophobic film according to claim 1, characterized in that: The steps of the preparation method of the I-III-VI multi-element quantum dot microspheres are as follows: (1) adding Ag-In-Zn-S quantum dot nanoparticles into dichloromethane, and then into a hexadecyltrimethylammonium bromide solution, heating to 70-80° C. and keeping the temperature for 25-35 minutes to obtain a modified Ag-In-Zn-S quantum dot solution; (2) The modified Ag-In-Zn-S quantum dot solution prepared in step (1) is mixed with a NaOH aqueous solution, heated and mixed at 70 to 90° C. for 15 to 25 minutes, and then tetraethoxysilane and ethyl acetate are added, and stirring is continued for 7 to 9 hours. After the temperature is lowered to room temperature, the mixture is centrifuged and the obtained product is washed with anhydrous ethanol to obtain Ag-In-Zn-S quantum dot microspheres.
3. The anti-counterfeiting super-hydrophobic film according to claim 2, characterized in that: In step (1), the dosage of Ag-In-Zn-S quantum dot nanoparticles and hexadecyltrimethylammonium bromide is 1 g: 0.125 mol.
4. The anti-counterfeiting super-hydrophobic film according to claim 2, characterized in that: The concentration of the NaOH aqueous solution is 2 mol / L; the mass ratio of the Ag-In-Zn-S quantum dot nanoparticles to tetraethoxysilane is 1:60-600.
5. The anti-counterfeiting super-hydrophobic film according to claim 2, characterized in that: The mass ratio of Ag-In-Zn-S quantum dot nanoparticles to tetraethoxysilane is 1:200-300.
6. The method for preparing the anti-counterfeiting super-hydrophobic film according to any one of claims 1 to 5, characterized in that: (1) adding Ag-In-Zn-S quantum dot microspheres, a silane coupling agent, and a fluorinated surfactant into ethyl acetate, and uniformly dispersing them by ultrasonic vibration to obtain an anti-counterfeiting dispersion; (2) Spraying the anti-counterfeiting dispersion onto a polyimide substrate and drying the resulting film to obtain a super-hydrophobic composite film having anti-counterfeiting properties.
7. The method for preparing the anti-counterfeiting super-hydrophobic film according to claim 6, wherein: The silane coupling agent is one or more of trimethoxy (3,3,3-trifluoropropyl) silane, 1H,1H,2H,2H-perfluorodecyl triethoxy silane, and trimethoxy (1H,1H,2H,2H-tridecafluorooctyl) silane.
8. The method for preparing the anti-counterfeiting super-hydrophobic film according to claim 6, wherein: The fluorine-containing surfactant is one or more of perfluorohexylethyl sulfonic acid, hexafluoroisopropanol, and perfluorooctylethyl acrylate.
9. The method for preparing the anti-counterfeiting super-hydrophobic film according to claim 6, wherein: The mass ratio of Ag-In-Zn-S quantum dot microspheres, silane coupling agent and fluorine-containing surfactant is 1:0.5-2:1-3.
10. The method for preparing the anti-counterfeiting super-hydrophobic film according to claim 6, characterized in that: The drying is carried out at 80 to 90°C for 5 to 7 hours.
Citation Information
Patent Citations
Fluorescent super-hydrophobic composite film taking fluorinated quaternary quantum dots as fluorescent material and preparation method of fluorescent super-hydrophobic composite film
CN118240255A